2018
DOI: 10.1039/c8cc01863d
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective amide reductions by heteroleptic fluoroaryl boron Lewis acids

Abstract: The heteroleptic borane catalyst (C6F5)2B(CH2CH2CH2)BPin is found to hydrosilylatively reduce amides under mild conditions. Simple tertiary amides can be reduced using Me2EtSiH, whereas tertiary benzamides required a more reactive secondary silane, Et2SiH2, for efficient reduction. The catalytic system described exhibits exceptional chemoselectivity in the reduction of oligoamides and tolerates functionalities which are prone to reduction under similar conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…. Moreover, its ability to activate hydrosilanes in the presence of oxygenated substrates by the Piers mechanism enables unique C–O-based catalysis. Another perfluoroarylborane, HB­(C 6 F 5 ) 2 (Piers’ borane), , has been directly utilized for selective deoxygenation reactions or as a precursor to other fluoroarylborane Lewis acids, taking advantage of its alkene and alkyne hydroboration abilities to assemble diverse catalysts. , Less used are the homoleptic tris­(trifluorophenyl)­boranes, BAr 2,4,6‑F and BAr 3,4,5‑F , which are weaker Lewis acids. , Compared to B­(C 6 F 5 ) 3 , B­(3,5-CF 3 ) 2 C 6 H 3 ) 3 (BAr 3,5‑CF3 ) is a little stronger by the Gutmann–Beckett method but presents as the weaker Lewis acid using the Childs method. , Although computations show BAr 3,5‑CF3 to be intrinsically weaker than B­(C 6 F 5 ) 3 , the absence of ortho -F groups creates a more sterically accessible boron site and, of interest to us, the possibility of purturbing the selectivity of challenging C–O activation reactions through catalyst choice.…”
mentioning
confidence: 99%
“…. Moreover, its ability to activate hydrosilanes in the presence of oxygenated substrates by the Piers mechanism enables unique C–O-based catalysis. Another perfluoroarylborane, HB­(C 6 F 5 ) 2 (Piers’ borane), , has been directly utilized for selective deoxygenation reactions or as a precursor to other fluoroarylborane Lewis acids, taking advantage of its alkene and alkyne hydroboration abilities to assemble diverse catalysts. , Less used are the homoleptic tris­(trifluorophenyl)­boranes, BAr 2,4,6‑F and BAr 3,4,5‑F , which are weaker Lewis acids. , Compared to B­(C 6 F 5 ) 3 , B­(3,5-CF 3 ) 2 C 6 H 3 ) 3 (BAr 3,5‑CF3 ) is a little stronger by the Gutmann–Beckett method but presents as the weaker Lewis acid using the Childs method. , Although computations show BAr 3,5‑CF3 to be intrinsically weaker than B­(C 6 F 5 ) 3 , the absence of ortho -F groups creates a more sterically accessible boron site and, of interest to us, the possibility of purturbing the selectivity of challenging C–O activation reactions through catalyst choice.…”
mentioning
confidence: 99%
“…Finally, a few functionalizations of the isoindolinone 2a have been demonstrated as well (Scheme ). Treatment of 2a with lithium diisopropylamide (LDA) at −78 °C followed by the addition of alkyl bromide can give the 3-substituted isoindolinones 3 , an important skeleton in biologically active compounds exhibiting antipsychotic, antihypertensive, antiulcer, and anxiolytic properties . The reaction of 2a with allyl bromide and phenyl bromide provided good yields of 3a (82%) and 3b (63%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that heteroleptic perfluoroaryl/alkyl borane catalysts, such as B 2 -Cat , are highly selective for amide reductions relative to their homoleptic counterparts (i.e., B­(C 6 F 5 ) 3 ). Given the successful application of heteroleptic borane catalysts on substrates with the complexity of di- and tripeptides, we questioned whether they may also enable site-selective reductions in complex polyamide substrates, and that these reductions would then enable additional structural modifications.…”
mentioning
confidence: 94%